Experience Marketing Strategy for West Java Aviation School Attracts Gen Z Interest - Dede Ardian; Miko Andi Wardana; Safitri Era Globalisasi; Rangga Maulana (Jurnal Informatika Ekonomi Bisnis, 2026)
This study examined the role of experience marketing strategies in attracting Generation Z’s interest in aviation schools in West Java, with a particular focus on social media content and virtual reality (VR) tour experiences. The rapid growth of aviation education institutions in West Java has intensified competition, prompting schools to adopt experiential marketing approaches that emphasize immersive and interactive engagement. A quantitative explanatory approach was employed by collecting data from 215 Generation Z respondents who were prospective students of aviation schools in West Java. Data were gathered through a structured questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicated that experiential social media content had a significant positive effect on brand experience and interest in enrolling, while virtual reality tours significantly enhanced perceived experiential value and institutional attractiveness. Furthermore, brand experience was found to mediate the relationship between experience marketing strategies and Generation Z’s enrollment interest. The findings highlight the importance of integrating digital experiential tools into marketing strategies for aviation education institutions to strengthen competitiveness and support the development of aviation human resources in West Java.